Virtual Frontiers: A Systematic Literature Review of Factors Shaping the Metaverse Readiness in Higher Education - Erianda, Aldo; Dalim, Che Samihah Che; Hidayat, Rahmat; Putra, Panca Okta Hadi (Journal of Applied Science, Engineering, Technology, and Education, 2026)
The potential of the Metaverse to create immersive learning spaces in higher education is promising, but the implementation complexities pose an enormous challenge. There is little to no research concerning the Metaverse component readiness gap. Most of the studies that do exist are either too focused on the technological factors of the Metaverse (as in the simple extensions of VR/AR, the 3D graphical environments) or address the technological access, the user’s VR/AR attitudes, or the infrastructure in isolation, without merging the technological, organizational, and environmental dimensions of the issue into one framework. Following the guidelines of the PRISMA methodology, 32 documents, which were indexed in Scopus, were systematically identified, and thematic analysis was conducted to elaborate the factors influencing the readiness for the implementation of the Metaverse. The literature synthesis yielded ten themes or factor clusters influencing Metaverse readiness in higher education: Immersive Learning Experience (ILE), System & Service Quality (SQ), Perceived Performance Value (PPV), Ease, Simplicity & Learnability (ESL), Risk, Security & Concerns (RSC), Personal Readiness (PR), Affective & Motivational Factors (AMF), Pedagogical & Knowledge Competence (PKC), Social Influence & Norms (SIN), and Institutional Support & Facilitating Conditions (ISFC). These findings contribute to the body of relevant literature and useful frameworks to assess metaverse readiness in higher education.